2018
DOI: 10.3390/md16040109
|View full text |Cite
|
Sign up to set email alerts
|

Makaluvamine G from the Marine Sponge Zyzzia fuliginosa Inhibits Muscle nAChR by Binding at the Orthosteric and Allosteric Sites

Abstract: Diverse ligands of the muscle nicotinic acetylcholine receptor (nAChR) are used as muscle relaxants during surgery. Although a plethora of such molecules exists in the market, there is still a need for new drugs with rapid on/off-set, increased selectivity, and so forth. We found that pyrroloiminoquinone alkaloid Makaluvamine G (MG) inhibits several subtypes of nicotinic receptors and ionotropic γ-aminobutiric acid receptors, showing a higher affinity and moderate selectivity toward muscle nAChR. The action of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Point mutations to mouse muscle nAChR were introduced as described previously [ 6 ]. Calcium fluorescence has been measured using the Case 12 genetically encoded sensor as described by Shelukhina [ 7 ] in 96-well plates to evaluate dose–response relationship and using the epifluorescent microscope set-up to study calcium rise amplitudes and exponential decay kinetics ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Point mutations to mouse muscle nAChR were introduced as described previously [ 6 ]. Calcium fluorescence has been measured using the Case 12 genetically encoded sensor as described by Shelukhina [ 7 ] in 96-well plates to evaluate dose–response relationship and using the epifluorescent microscope set-up to study calcium rise amplitudes and exponential decay kinetics ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Such conditions are not human-specific but also affect other mammals such as dogs, cats [ 5 ], and rodents [ 1 ]. Among congenital myasthenic conditions, the group caused by dominant gain-of-function mutations, called slow-channel myasthenic syndromes (SCCMSs), attracted previously our attention [ 6 , 7 ]. SCCMS have long history in translational medicine research.…”
Section: Introductionmentioning
confidence: 99%
“…In our recent work on low molecular weight compounds (Kudryavtsev et al, 2018;Spirova et al, 2019), a-conotoxins (Kudryavtsev et al, 2015;Kasheverov et al, 2016;Kryukova et al, 2018a), and human Ly6 proteins (Lyukmanova et al, 2016;Durek et al, 2017), we found that some of them can bind to the orthosteric or allosteric sites of nAChRs. Here we did not plan a detailed investigation of the mechanism of oligoarginine action, but we made exceptions for R8 and W2R4.…”
Section: Discussionmentioning
confidence: 95%
“…In 2009, Wang et al [ 81 ] synthesized a marine-derived makaluvamine analog, named 7-(4-fluorobenzylamino)-1,3,4,8-tetrahydropyrrolo[4,3,2-de]quinolin-8(1H)-one (FBA-TPQ). Makaluvamines are produced by marine sponges [ 82 ]. FBA-TPQ showed a dose-dependent cytotoxicity in human PC3 and LNCaP cells, with IC50 of 0.79 μM, 0.42 μM, and TRAMPC1 murine prostate cancer cells, with IC50 of 0.26 μM.…”
Section: Marine Macroorganismsmentioning
confidence: 99%